Abraham im Werk des Lukas: Seine theologische Bedeutung, narrative Gestaltung und literarische Funktion - Kreitschmann, Eva-Maria (Wissenschaftliche Untersuchungen zum Neuen Testament 2. Reihe, 2026)
Luke demonstrates a pronounced theological and narratological interest in the figure of Abraham. In his narrative, he reinterprets the important Jewish theological theme of the Abrahamic covenant as salvation from affliction, renewed justice, and a restored relationship with God in Israel. Using the figure of Abraham, Luke creates a coherent narrative thread through which he retells the story of Jesus.